Community Compliance Level To Health Policy To Prevent Covid-19 - Alfisa Her Bening (International Journal of Health Science and Technology, 2021)
Title : Community compliance level to health policy to prevent covid-19. Purpose: This study identified the level of compliance toward the COVID-19prevention health protocols among the Tegalrejo District community. Methods: This descriptive study used an accidental  design, distributing closed questions in a google form questionnaire accidentally to 110 respondents on social media. Data were analyzed univariately by calculating the frequency, percentage and cross tabulation. Results: Most of the respondents did not comply with the COVID-19prevention health protocol (95.5%) because there had been a cognitive bias in the community.